Death of the social self? Comparing the effects of ostracism to mortality salience - Rachel S. Taggart; Maayan Dvir; Janice R. Kelly; Eboni S. Bradley; Kipling D. Williams (Social Influence)
The ‘social death’ metaphor is used to reflect ostracism’s severity and death-related themes often influence ostracism research. To determine its accuracy, we examined the similarity of ostracism and mortality salience (MS) outcomes. To manipulate these constructs, we used writing prompts in Study 1, and Cyberball and a novel MS manipulation, ‘Cybergrave,’ in studies 2, 3a, and 3b. In Study 4, we correlated chronic ostracism and death-thought accessibility. Ostracism uniquely threatened psychological needs, whereas MS uniquely activated death thoughts. Moreover, the correlation between chronic ostracism and death-thought accessibility was small and non-significant when controlling for related variables. Results suggest the death metaphor may not always be accurate. Death-related language may bias how ostracism is conceptualized and studied, emphasizing pain over recovery.